From Doctrine to Implementation: Governance of National Resource Mobilization in Indonesia’s Defense System - Agung Udayana; Purnomo Yusgiantoro; Jonni Mahroza; Jati Bambang Priyambodo (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
National resource mobilization constitutes an integral component of Indonesia’s defense system, which adopts a total defense framework. Although doctrinal and policy frameworks have been formulated with relative consistency, the implementation of national resource mobilization remains constrained at the operational level. This article examines the gap between policy formulation and implementation by focusing on the governance mechanisms that shape national resource mobilization. Employing a qualitative approach based on policy analysis, defense strategic documents, and a review of implementation practices in non-military defense contexts, this study identifies key implementation constraints. The findings indicate that fragmented institutional authority, weak cross-sectoral coordination mechanisms, and the absence of institutionalized civil–military operational procedures significantly limit effective national resource mobilization. This article argues that the effectiveness of total defense is determined less by doctrinal completeness than by the capacity of implementation governance.